PERCEPTIONS OF EDUCATION ROLE IN DEVELOPING SOCIETY - Farmonova, Maftuna Odil qizi; Ikramova , Xurshida Azamatovna (Innovative Development in Educational Activities, 2022)
This article discusses the importance and problems of study and education’s place in our community.